2010
DOI: 10.1080/09537320903498546
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exchange behaviours of science park firms: the innovation hub case

Abstract: Knowledge exchange behaviours of science park firmsChan, K.Y.; Oerlemans, Leon; Pretorius, M.W. General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
(41 reference statements)
0
28
0
4
Order By: Relevance
“…Some studies indicate that ISTPs strengthen inter-organizational relations (Chan et al, 2010;Phillimore, 1999;Tan, 2006;Vedovello, 1997) and innovation (Lindelöf & Löfsten, 2003;Tan, 2006). In Brazil, for instance, Lahorgue (2004) and Etzkowitz et al (2005) indicated that incubators have been producing encouraging results in terms of generating employment and income for the population.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that ISTPs strengthen inter-organizational relations (Chan et al, 2010;Phillimore, 1999;Tan, 2006;Vedovello, 1997) and innovation (Lindelöf & Löfsten, 2003;Tan, 2006). In Brazil, for instance, Lahorgue (2004) and Etzkowitz et al (2005) indicated that incubators have been producing encouraging results in terms of generating employment and income for the population.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent empirical studies have led to doubts regarding the effectiveness of SPs. Evidence has indicated that SPs are ineffective in establishing knowledge linkages with local research institutes, stimulating regional technology development, increasing profits and employment (see for example, Garnsey and Heffernan, 2005;Chen, 2009;Chan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A relação entre redes e conhecimento encontra suporte no argumento de Shieh-Chieh, Fu-Sheng e Lin (2010), segundo os quais a participação na rede e o compartilhamento de conhecimento devem ser mecanismos de aprendizagem complementares e de igual importância, que promovem a inovação em empresas incubadas. O conhecimento, ou seu processo de transferência e acumulação, é, em geral, considerado uma importante dimensão de análise (Bigliardi, Dormio, Nosella, & Petroni, 2006;Hansson et al, 2005;Harper & Georghiou, 2005;Hu, Lin, & Chang, 2005;Kai-Ying et al, 2010).…”
Section: Complementaridade De Conhecimentosunclassified
“…Abordada na literatura sobre colaboração como a complementaridade moderada das bases de conhecimento (Nooteboom, 2008;Schoenmakers & Duysters, 2006), como "conhecimento tecnológico relacionado" ou "proximidade tecnológica" (Kai-Ying et al, 2010), a sinergia foi relativamente pouco explorada na literatura empírica, embora tenha sido cultivada em estudos seminais como os de Saxenian (1994) A literatura empírica também aponta recursos oferecidos por esses ambientes que podem favorecer a complementaridade de conhecimentos e a sinergia entre as empresas, subsidiando as próximas proposições do presente estudo. Por exemplo, laboratórios para P&D e literatura especializada (Harper & Georghiou, 2005;Hsien-Che & Shyu, 2005;Löfsten & Lindelöf, 2005;Vedovello, 1997), assim como equipamentos e instalações (Kihlgren, 2003;Malairaja & Zawdie, 2008;Watkins-Mathys & Foster, 2006), são considerados recursos que atuam nesse sentido.…”
Section: Complementaridade De Conhecimentosunclassified
See 1 more Smart Citation